Influence of sol and deposition method in developing TiO2 brookite coatings - Suzaim, Farah Hanum (2021)
Brookite is highly promising photocatalyst due to its high photoactivity performance and significant hydrophilic ability. However, the development and application of pure sol-gel brookite coating is less reported. Therefore, the main objective of this research is to deposit brookite TiO2 sol-gel coatings derived from ‘green formulated sol’ for self-cleaning application. The TiO2 coatings were fabricated from various hydrolysis ratio, temperatures and deposition method. The hydrolysis ratio of water to titanium (IV) isopropoxide (TTiP) used are 32:4 (W32), 48:4 (W48) and 64:4 (W64). In this work, two deposition methods which are dip and spin coating are used to compare the influence of deposition methods on TiO2 coating phase formation, particularly on identifying the brookite presence. The deposited TiO2 coatings were then heated at various temperatures such as 200 °C, 300 °C, 400 °C and 500 °C and soaked for 3 hours. For phase analysis, X-ray diffraction (XRD) and Raman spectroscopy are used to examine the influence of sol and deposition method towards phase formation. The surface and cross sectional morphological of TiO2 coating were analyzed by scanning electron microscope (SEM) observation. The crystallite size was calculated using Scherrer’s equation. The optical and hydrophilic properties were conducted to examine the TiO2 coating characteristic. Results show that the different sol formulations and deposition methods have an influence in brookite TiO2 coating’s development. XRD result indicate that a single peak emerged at 31.9° from spin method was referred to the (111) plane of brookite crystal. For the spin coating, Raman spectroscopy also indicate a dominant brookite characteristic (band at 322 cm−1 and 363 cm−1). SEM analysis revealed that the spin coating produced a uniform coating compared to the dip coating. Besides, the surface coating of the deposited TiO2 coating via dip coating showed cracks regardless of temperature used. The thickness of the TiO2 coating via spin coating is thinner (447 nm) compared to the dip coating (887 nm). The crystallite size of the TiO2 spin coating was larger (63.2 nm) compared to the crystallite size of the spin coated (18.7 nm). The band gap value of the TiO2 spin coating was in the range of 3.32 eV - 3.46 eV (brookite characteristic) whereas for the TiO2 dip coating, their band gap value was in the range of 3.05 eV - 3.18 eV (anatase characteristic). Furthermore, the TiO2 spin coating exhibited more hydrophilic characteristic compared to the TiO2 dip coating. For photoactivity performances, the brookite TiO2 coating was found to be more effective in the degradation of methylene blue (90.65%) and photo-induced hydrophilicity (15.21°). As a conclusion, it is found that spin coating deposition with W64 sol formulation is preferable for brookite formation whereas dip coating is more suitable for anatase and rutile.